FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL MEDIASI - Nadia Pricillia; Henryanto Wijaya (Fakultas Ekonomi, Universitas Tarumanagara, 2026)
This research aims at how the role of institution ownership , managerial ownership, independent director, and firm size on firm value with financial performance as a mediating variable. This research was conducted by taking 45 samples from non-state-owned enterprises healthcare companies and listed in IDX from 2019-2021. Sample was selected using purposive sampling method and SmartPLS 4.0.8.4 is used to analyze data. The results of this study indicate that financial performance has a significant effect on firm value while institutional ownerhsip, managerial ownership, independent director and firm size has not significant effect on firm value. Besides, financial performance can’t mediate the effect of institutional ownership, managerial ownership, independent director and firm size on firm value. The implication of this study is managerial ownership and independent of director must be increase so they can act as investor expect.